The challenges for Chinese FDI in Europe - Louis Brennan (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
This Perspective addresses Chinese foreign direct investment in Europe. It focuses on the major challenges that Chinese investors have faced in that host environment. These relate to the host region's divergent characteristics, home country liability of origin, China's OFDI regulation and the capabilities of the investing enterprises.
Keywords: 330